2018
DOI: 10.1016/j.cub.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Parasitoids Turn Herbivores into Mutualists in a Nursery System Involving Active Pollination

Abstract: Nursery pollination involves pollinators that lay eggs on the flowers they pollinate and have their brood fed on flower parts or developing ovules [1-4]. Active pollination, a ritualistic behavioral sequence shown by nursery pollinators when transferring pollen from anthers to stigmas, is known in only four plant lineages [5-8], including the classical examples of fig trees-fig wasps and yuccas-yucca moths [5, 6]. We report in detail a system in which weevils actively pollinate orchids prior to having their la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…Likewise, in the related plant genus Phyllanthus, almost 60% of developing Epicephala larvae were killed by braconid wasps, which resulted in increased net seed production (Kawakita & Kato, 2004a). Furthermore, the killing of pollinator larvae by parasitoids in several other non-Epicephala OPMs is also known to promote plant reproductive fitness (Dunn et al, 2008;Nunes et al, 2018). It may be that some of the parasitoid species that attack Epicephala on B. oblongifolia are koinobionts, i.e.…”
Section: Parasites and Parasitoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, in the related plant genus Phyllanthus, almost 60% of developing Epicephala larvae were killed by braconid wasps, which resulted in increased net seed production (Kawakita & Kato, 2004a). Furthermore, the killing of pollinator larvae by parasitoids in several other non-Epicephala OPMs is also known to promote plant reproductive fitness (Dunn et al, 2008;Nunes et al, 2018). It may be that some of the parasitoid species that attack Epicephala on B. oblongifolia are koinobionts, i.e.…”
Section: Parasites and Parasitoidsmentioning
confidence: 99%
“…In addition to pollinators, the fruits of plants involved in OPMs may host various non-pollinating seed predators, parasitoids and hyperparasitoids. Parasitoids can play a direct role in reducing seed herbivory and promoting plant reproductive fitness by killing developing pollinators (Kawakita & Kato, 2004a;Kawakita & Kato, 2004b;Dunn et al, 2008;Nunes et al, 2018). Furthermore, seeds may be consumed by other, non-pollinating seed predators, which are unrelated to pollinators.…”
Section: Introductionmentioning
confidence: 99%
“…Dufaÿ and Anstett (2003) reviewed nursery pollination systems and described a total of 13 documented cases, although since then other systems have been discovered (see Kawakita & Kato, 2004; Nunes, Maruyama, Azevedo‐Silva, & Sazima, 2018; Song et al, 2014). Within these systems, there are some which are obligate mutualisms, such as the interaction between Ficus trees and fig wasps, Yucca and yucca moths, or senita cacti and senita moths (Anstett, Bronstein, & Hossaert‐McKey, 1996; Dufaÿ & Anstett, 2003; Holland & Fleming, 1999; Pellmyr et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In an empirical case study, though not of a nursery pollination system, van Loon, Boer, and Dicke (2000) found that parasitization of the herbivore Pieris rapae significantly reduced seed loss of its host plant Arabidopsis thaliana , suggesting that parasitism of herbivores potentially increased plant fitness. In that line, a study by Nunes et al (2018) described a new nursery pollination system formed by a weevil and its orchid host plant, in which parasitoid wasps mediated the outcome of the interaction by killing the weevil larvae and therefore changing the cost/benefit ratio of the partnership. Moreover, very recently Stucchi, Giménez‐Benavides, and Galeano (2019) developed a population dynamics model demonstrating how the Silene–Hadena system might be more stable in the presence of parasitoids.…”
Section: Introductionmentioning
confidence: 99%
“…Active pollination has evolved in yucca moths (Riley, ; Pellmyr, ), fig wasps (Ramirez, ; Weiblen, ; Herre et al., ), leafflower moths (Kato et al., ; Kawakita and Kato, ), and senita moths (Fleming and Holland, ; Holland and Fleming, ). Recently, active pollination has also been discovered in weevils that pollinate orchid species (Nunes et al., ) and in heliozelid moths that pollinate Boronia (Rutaceae) in Australia (Milla, ). In all of these species, females actively collect pollen from flowers via specialized behaviors and morphologies.…”
mentioning
confidence: 99%